2019 Kansas Summer Annual Forage Hay and Silage Variety Trial - J. D. Holman; A. K. Obour; J. Lingenfelser; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2020)
In 2019, summer annual forage variety trials were conducted across Kansas near Garden City, Hays, and Scandia. All sites evaluated hay and silage entries. Companies were able to enter varieties into any possible combinations of research sites, so not all sites had all varieties. Across the sites, a total of 95 hay varieties, 99 sorghum silage varieties, and 12 corn silage varieties were evaluated.
Keywords: forage; hay; sorghum silage; corn silage